Technological interventions in improving the functionality of proteins during processing of meat analogs - Kumar, Pavan; Sharma, Neelesh; Ahmed, Muideen Adewale; Verma, Akhilesh K.; Umaraw, Pramila; Mehta, Nitin; Abubakar, Ahmed Abubakar; Hayat, Muhammad Nizam; Kaka, Ubedullah; Lee, Sung-Jin; Sazili, Awis Qurni (Frontiers in Nutrition, 2022)
Meat analogs have opened a new horizon of opportunities for developing a sustainable alternative for meat and meat products. Proteins are an integral part of meat analogs and their functionalities have been extensively studied to mimic meat-like appearance and texture. Proteins have a vital role in imparting texture, nutritive value, and organoleptic attributes to meat analogs. Processing of suitable proteins from vegetable, mycoproteins, algal, and single-cell protein sources remains a challenge and several technological interventions ranging from the isolation of proteins to the processing of products are required. The present paper reviews and discusses in detail various proteins (soy proteins, wheat gluten, zein, algal proteins, mycoproteins, pulses, potato, oilseeds, pseudo-cereals, and grass) and their suitability for meat analog production. The review also discusses other associated aspects such as processing interventions that can be adapted to improve the functional and textural attributes of proteins in the processing of meat analogs (extrusion, spinning, Couette shear cell, additive manufacturing/ 3D printing, and freeze structuring). `